(untitled) - Okimoto, Daniel I. (Stanford, Calif., 1989)
Over the postwar period, the scope of industrial policy has expanded markedly. Governments in virtually all advanced industrial countries have extended the visible hand of the state in assisting specific industries or individual companies. Although greater government involvement in some countries has lessened the dislocations brought about by slower growth rates, industrial policy has also caused or exacerbated a number of other problems, including distortions in the allocation of capital and labor and trade conflicts that undermine the postwar system of free trade.
Keywords: High technology industries,Các ngành công nghệ cao; Government policy,Chính sách của chính phủ; Japan,Nhật Bản